2015
DOI: 10.1097/ico.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

Iontophoretic Transepithelial Corneal Cross-linking to Halt Keratoconus in Pediatric Cases

Abstract: Transepithelial collagen cross-linking by iontophoresis, unlike other transepithelial techniques, seems to halt pediatric keratoconus progression over 15 months. However, we did not record significant improvement in higher-order aberrations and topographic indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 23 publications
0
32
0
2
Order By: Relevance
“…Plus, they confirmed that this Epi-ON protocol resulted in keratoconus evolution after 24 months of follow-up, adding a note of caution to its application in pediatric patients that often suffer from more aggressive forms of the disease 32 . Indeed, as for other transepithelial protocols, iontophoresis does not seem to ensure an improvement in topographic indices in pediatric patients 33 . This absence of efficacy can be explained by limited riboflavin and UVA penetration with the epithelium in situ 11,[34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Plus, they confirmed that this Epi-ON protocol resulted in keratoconus evolution after 24 months of follow-up, adding a note of caution to its application in pediatric patients that often suffer from more aggressive forms of the disease 32 . Indeed, as for other transepithelial protocols, iontophoresis does not seem to ensure an improvement in topographic indices in pediatric patients 33 . This absence of efficacy can be explained by limited riboflavin and UVA penetration with the epithelium in situ 11,[34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…For iontophoresis, up to 15-month followup data have been published, with reported cessation of disease progression and improvements in keratometric and visual parameters. [7][8][9] The longer-term relative efficacy of all these transepithelial techniques compared to epithelium-off CXL remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Another method involves iontophoresis, in which negatively charged riboflavin is driven through the epithelium down an electrical gradient. [7][8][9] Previous studies to quantify riboflavin penetration through an intact epithelium have used high-performance liquid chromatography (HPLC) [10][11][12] and fluorescence microscopy. [13][14][15][16][17] High-performance liquid chromatography, in which the sample is dissolved in a solvent for analysis, can accurately quantify the concentration of riboflavin in a whole block of tissue, but is unable to provide information about the concentration at different depths within the corneal stroma (unless lamella sections are prepared and separately dissolved).…”
mentioning
confidence: 99%
“…Исход лечения характеризовался существенным улучшением функци-ональных показателей, основанных на специфичных морфологических изменениях в роговице [78]. Хорошие результаты продемонстрировала трансэпителиальная техника CXL, выполненная у подростков от 10 до 18 лет с помощью ионофореза в ускоренном режиме облучения (5 мин, 10 мВт/см 2 ) [79].…”
Section: возможности клинического применения уф-кросслинкингаunclassified